Research of the Fault Feature Extraction of the Transmission Weak Abnormal Sound based on the Sample Entropy - Wu Chao; Sun Huer; Liang Xiaohua (Jixie chuandong)
Aiming at the weak abnormal sound of the new transmission products in the specific speed range of gear,the nonlinear of the dynamic parameter sample entropy is used to extract the operating characteristics of the transmission under different gears. The influence of different parameters on the sample entropy extraction is researched. The appropriate parameters are selected to calculate the sample entropy. In this parameter,the sample entropy and approximate entropy of the normal gear and fault gear are analyzed. The results show that with the input shaft rotational speed increasing,the sample entropy of the normal gear changes little,but the sample entropy of the fault gear decreases. And sample entropy compared to approximate entropy can be more effective extraction of transmission gear characteristics. And the order envelope analysis is carried out for the failure of the fourth gear of a transmission with abnormal sample entropy,and the fault diagnosis of transmission gear is realized.